STRUKTUR DIMENSI KEPRIBADIAN TOKOH DALAM NOVEL PLANET LUNA KARYA RAY ANTARIKSA YASMINE - oktaviana, fazra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to analyze the structure of personality dimensions in the novel Planet Luna by Ray Antariksa Yasmine. The research method used is descriptive with a qualitative approach, and data was collected through documentary study techniques. The data source is the novel Planet Luna, and the data analyzed includes words, phrases, sentences, and dialogues found within the novel. The results of the study show, first, the extraversion personality traits found in the characters of the novel Planet Luna, including friendly, lively, active, assertive, sensation-seeking, cheerful, dominant, enthusiastic, and brave traits; second, the neuroticism personality traits, including anxious, depressed, guilty, low self-esteem, tense, irrational, shy, gloomy, and emotional traits; third, the psychoticism personality traits, including aggressive, cold, egocentric, impersonal, impulsive, antisocial, unempathetic, creative, and tough traits; Fourth, the study also results in the development of a text-based teaching module from the novel Planet Luna as a learning material for 12th-grade senior high school students.